Technology factors related to the differences in paper and online reading scores in PIRLS 2016 - Plamen V. Mirazchiyski; Vadim Gershteyn (Large-scale Assessments in Education, 2024)
Abstract The Progress in International Reading Literacy Study (PIRLS) was conducted in paper and online reading modes in 2016 using the same samples of students in a number of countries. Differences in reading literacy scores were found in several European countries. In some countries, the differences favored the electronic reading mode. Yet in others, the paper reading mode was favored. As the electronic reading mode differs substantially in the cognitive demands compared to the paper mode, it can be expected that the differences between the two modes are related to the variables related to technology: availability and access, general use, use for educational purposes in class or out-of-school, and self-efficacy with technology. This study investigates the Information and Communication Technology (ICT) factors related to the differences in paper and online reading in six European countries participating in both modes in PIRLS 2016. This study uses linear regression models as the application of multilevel modeling is not suitable because of the low between-school variances across countries. The results from this study show limited support for the relative effect that the student individual, school, and classroom ICT variables have on the differences between paper and electronic reading. Access to technology is related to mode differences only in Italy, and the use of computer devices in and out of school is related to the mode differences in Italy and Portugal. Student self-efficacy is related to the mode differences in Portugal and Slovenia. School resources show significant effects in Denmark (computers to students ratio) and Italy (instruction affected by digital resource shortages). None of the classroom variables showed any significant relationship in any of the countries. In addition, socio-economic status (which is proxied by the variable on home resources for learning) is a significant predictor in half of the countries. In addition to these findings, the general technological context within countries is discussed as part of an evaluation of the difference in reading in the two test delivery modes. The general uptake of technology in different social and economic aspects, as measured by the Digital Economy and Society Index (DESI), follows the differences between the two reading modes.